Newspapers and disaster risk reduction in Nigeria: A review - Adekunle, Ganiyu Mutiu; Mohammed, Rosli; Ismail, Awan (2016)
The main purpose of the paper is to discuss the media role in disaster risk reduction.The role of mass media in the society cannot be overstated. It has been identified as a key stakeholder as it informs, educates, mobilizes, and entertains among other roles.As an agent of development, media is identified as a crucial factor in disaster management.The paper examines the role being played by Nigerian newspapers in curbing flood devastation.With the growing frequency and devastation of flood disaster globally and in Nigeria in particular, the need for all stakeholders to collaborate is more urgent. In Nigeria, flood is the commonest disaster and a perennial problem.However, as crucial as finding solutions to this problem is, few researches have been conducted on the role of media in disaster risk reduction.The review reveals that Nigerian media is not proactive but reactive in its involvement.Findings show that media largely get involved during and after disaster occurrences, reporting human misery, tragedy loss of lives and property.Also, it is confirmed that rather than seeing self as a vital stakeholder, media still considers self as observer or passive participant. The study concludes by calling on the media to collaborate more with other stakeholders, disseminate early warning information, educate populace ahead of flood incidents and play other vital roles to complement other stakeholders efforts in reducing disaster risks.